"Knock Knock": a qualitative study exploring the experience of household contacts on home visits and their attitude towards people living with TB in South Africa - Farzana Sathar; Kavindhran Velen; Meaghan Peterson; Salome Charalambous; Candice M. Chetty-Makkan (BMC, 2020)
Abstract Background Household contract tracing (HHCT) is an important strategy for active tuberculosis case finding and offers an opportunity for testing of other diseases such as HIV. However, there is limited data on the patient-centered approach to HHCT. Our study aimed to describe experiences and preferences of household contacts (HHCs) for HHCT. Methods We conducted a qualitative study in Rustenburg, South Africa from September 2013 to March 2015. Twenty-four HHCs (≥18 years) had audio-recorded in-depth interviews. We used an inductive thematic analysis approach to develop themes. We made an a priori assumption that we would reach saturation with at least 20 interviews. Results There were 16 (66.7%) females (median age = 36 years) and eight (33.3%) males (median age = 34 years). Two themes developed: (i) Positive attitude of HHCs towards TB services provided at home and (ii) HHCs relationship to and acceptance of people living with TB (PLTB). The first main theme emphasized that HHCs appreciated the home visits. Participants preferred home visits because they had negative experiences at the clinic such as delayed waiting times and long queues. HHCs supported the screening of children for TB at home. Participants suggested that the research staff could expand their services by screening for diabetes and hypertension alongside TB screening. In the second main theme, there was a sense of responsibility from the HHCs towards accepting the diagnosis of PLTB and caring for them. A sub-theme that emerged was that as their knowledge on TB disease improved, they accepted the TB status of the PLTB empowering them to take care of the PLTB. Conclusions HHCs are supportive of HHCT and felt empowered by receiving TB education that ultimately allowed them to better understand and care for PLTB. HHCs were supportive of screening children for TB at home. Future HHCT activities should consider raising community awareness on the benefits of TB contact tracing at households.